Beneficial effect of n-3 polyunsaturated fatty acids on inflammation and analgesic use in psoriatic arthritis: a randomized, double blind, placebo-controlled trial. (2nd January 2018) - Kristensen, S; Schmidt, EB; Schlemmer, A; Rasmussen, C; Johansen, MB; Christensen, JH
Abstract : Objective : This study aimed to investigate the effects of marine n-3 polyunsaturated fatty acids (PUFAs) on disease activity, use of analgesics, and inflammatory biomarkers in patients with psoriatic arthritis (PsA). Method : Patients with established PsA (n = 145) were investigated in a randomized, double-blind, placebo-controlled study. The participants received a supplement of 3 g n-3 PUFA/day or 3 g olive oil/day (control) for 24 weeks. Outcome measures for disease activity, use of analgesics, and leukotriene formation from activated granulocytes were assessed at baseline and at study end. Results : In total, 145 patients were included and 133 completed the study. After 24 weeks, the n-3 PUFA group showed a decrease in Disease Activity Score (DAS28-CRP), 68 tender joint count, enthesitis score, and psoriasis area and severity index, although not significantly different from the controls. There was a significant reduction in non-steroidal anti-inflammatory drug (NSAID) and paracetamol use compared with controls (p = 0.04). In addition, the participants in the n-3 PUFA group had significantly lower formation of leukotriene B4 (p = 0.004) from stimulated granulocytes and significantly higher formation of leukotriene B5 (p < 0.001) compared with controls. Conclusion : The n-3 PUFA-supplemented group showed improvement in outcome measures for disease activity, although the difference between the groups was not statistically significant. However, use of NSAIDs and paracetamol was significantly reduced in the n-3 PUFA group compared to the control group. Finally, there was a significant decrease in leukotriene B4 formation in the n-3 PUFA group compared with controls.